1971
DOI: 10.1063/1.1674767
|View full text |Cite|
|
Sign up to set email alerts
|

Pyrene Dimer Cation as Studied by Pulse Radiolysis

Abstract: Radical cations of pyrene were investigated by the pulse radiolysis technique in solutions of benzonitrile, acetone, and dichloroethane. A 450-nm absorption band of a pyrene monomer cation was replaced by new bands with maxima at 500, 580, and 750 nm as the pyrene concentration was increased. The latter absorption bands were exclusively assigned to a pyrene dimer cation in equilibrium with the monomer cation at room temperature. Equilibrium constants evaluated were (2.7 ±0.2) X 10 2 and (5.1±0.5) X 102M~1 at 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0

Year Published

1972
1972
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 18 publications
4
43
0
Order By: Relevance
“…This tripl t state is considered to be produced by recombination of pyrene cation and the counter anion. However, the bands at 390nm and 510nm, indicating dimer cation formation, 16 were not detected.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…This tripl t state is considered to be produced by recombination of pyrene cation and the counter anion. However, the bands at 390nm and 510nm, indicating dimer cation formation, 16 were not detected.…”
Section: Resultsmentioning
confidence: 92%
“…Not only the singlet excimer but also the dimer cation is observed in intermolecular systems, and it was confirmed that the formation enthalpy of the latter was almost equal to that of the former. 16 In addition, intramolecular triplet excimer was observed in the compact geometry of bis[ 1-( lpyrenyl)ethyl]ethers.8 The differences between the present and other systems may be ascribed to geometrical structure of dipeptides. According to recent detailed fluorescence studies, 15 an excimer common to threo-and erythro-BIPyA is formed from two conformers in the ground state.…”
Section: Resultsmentioning
confidence: 97%
“…Particularly attractive among these are charged PAH clusters. However, because of the experimental inaccessibility of these highly unusual and reactive species, there is no gas phase spectroscopic data available to the best of our knowledge with which to test this hypothesis [PAH dimer cations have been characterized in solution (21,22) but are subject to strong solvation effects]. To make progress, we explore the spectroscopic properties of various charged PAH clusters by using ab initio quantum chemical calculations and show that a unique class of closed-shell charged dimers can account for the ERE.…”
Section: T He Extended Red Emission (Ere) Was Discovered In 1975 Bymentioning
confidence: 99%
“…9 The temperature was controlled by a flow of cooled or heated nitrogen gas in a thermostatic box with a thin aluminum window to admit the electron beam and a quartz evacuated cell as a window for the analyzing light beam.…”
mentioning
confidence: 99%